Intracellular Degradation of SARS-CoV-2 N-Protein Caused by Modular Nanotransporters Containing Anti-N-Protein Monobody and a Sequence That Recruits the Keap1 E3 Ligase - Yuri V. Khramtsov; Alexey V. Ulasov; Tatiana N. Lupanova; Tatiana A. Slastnikova; Andrey A. Rosenkranz; Egor S. Bunin; Georgii P. Georgiev; Alexander S. Sobolev (MDPI AG, 2023)
The proper viral assembly relies on both nucleic acids and structural viral proteins. Thus a biologically active agent that provides the degradation of one of these key proteins and/or destroys the viral factory could suppress viral replication efficiently. The nucleocapsid protein (N-protein) is a key protein for the SARS-CoV-2 virus. As a bioactive agent, we offer a modular nanotransporter (MNT) developed by us, which, in addition to an antibody mimetic to the N-protein, contains an amino acid sequence for the attraction of the Keap1 E3 ubiquitin ligase. This should lead to the subsequent degradation of the N-protein. We have shown that the functional properties of modules within the MNT permit its internalization into target cells, endosome escape into the cytosol, and binding to the N-protein. Using flow cytometry and western blotting, we demonstrated significant degradation of N-protein when A549 and A431 cells transfected with a plasmid coding for N-protein were incubated with the developed MNTs. The proposed MNTs open up a new approach for the treatment of viral diseases.